Management on the Silver Screen: Transforming Learning through Cinema - Kataria, Kalpana (Indian Journal of Educational Technology, 2025)
The present article aims to explore the existing literature available on the use of movies as a pedagogy to teach management in higher education, along with the discussion on the advantages and barriers to the use of movies as pedagogy for management education and also suggesting the scope use of movies to teach management in the Indian context. The literature review underscores the importance of research literature in identifying gaps and justifying investigations. To ensure quality, only peer-reviewed works from Scopus (2013-2024) were considered, resulting in 820 articles. Ten papers, meeting specific criteria and focusing on movies, pedagogy, teaching, management, and higher education, were ultimately selected for review. The inclusion criteria involved articles published exclusively in peer-reviewed journals and those written in English. The study reveals enhanced learning effectiveness with the use of movies as a teaching tool over traditional ones. Current-generation students exhibited heightened engagement and enjoyment with this way of learning. The study advocates for educators to use movies as a pedagogical tool for more interactive, experiential classrooms to leverage the benefits of this tool effectively. However, the study focuses solely on teaching a management course. This study is limited to the revisiting of existing literature concerning the use of movies as a pedagogical tool to teach management only from Scopus and Google Scholar. There are many other databases that can provide more insight into the context of novel dimensions applicable to the use of movies to teach management and other courses effectively in India. Movies as a pedagogical tool in higher education for management provide practical benefits, enhancing engagement, catering to diverse learning styles, and fostering cultural sensitivity. They bridge theory and application, promote critical thinking, and facilitate discussions on ethics, offering flexibility and cost-effectiveness. Movies as a pedagogical tool in higher education for management studies offer benefits such as enhanced engagement, accessibility, and diverse perspectives. However, challenges include stereotyping, misrepresentation, and a potential compromise in academic rigour, raising concerns about the limited realworld application and the interpretative nature of movies. This study navigates a literary quandary, championing roleplays’ educational efficacy yet acknowledging their waning relevance amid technological exposure. Uniquely, it delves into fostering increased student engagement, distinguishing itself through a focus on enhancing classroom participation.